INVESTIGATING STUDENTS ERRORS IN DESCRIPTIVE WRITING AT SECOND SEMESTER STUDENTS AT STIKES YARSI MATARAM - Danul Aristiawan (Journal of Languages and Language Teaching, 2019)
Analyzing the errors is one of the appropriate ways to use to show the true proficiency level of the target language that students learn at a particular time. By conducting analysis on grammatical errors, the teacher can conclude the most frequent of errors which are often made by students then, teachers can arrange the more effective and interesting strategies in teaching grammatical rules. This research was aimed to elaborate on kinds of students errors and possible causes of in writing a descriptive text. The instruments used for this research are writing tasks and questioner. This research was a descriptive qualitative method because the data of this research is in the form of sentences and paragraphs. The data gotten were then analyzed by using surface taxonomy strategy. The result of this research, It was found four types of errors in the students writing. Those are omission error, addition error, misformation error, and misordering error. Omission and misformation error is the most frequent of errors found in the text. Whereas, the sources of error found in this research are interlingual transfer, intralingual transfer, the context of learning and communication strategies. Based on the analysis researcher found that interlingual and context learning is the dominant cause of the error. The researcher can deliver suggestion especially to the teacher, they should give the clear explanation about the different rules both Indonesian and English, the teacher should emphasize the concepts of the verb tenses because the most frequent of errors relate to use subject-verb agreement.